A population of dermal Langerin+ dendritic cells promote the inflammation in mouse model of atopic dermatitis - Xiao, Chunying; Zhu, Zhenlai; Zhang, Chen; Gao, Jixin; Luo, Yixin; Fang, Hui; Qiao, Hongjiang; Li, Wei; Wang, Gang; Fu, Meng (Frontiers in Immunology, 2022)
Cutaneous dendritic cells (DCs) have been implicated in the pathogenesis of atopic dermatitis (AD); however, the role of specific subset of DCs has not been well defined. Here, we investigated the contributions of Langerhans cells (LCs), resident dermal Langerin+ DCs (r-Langerin+ dDCs) and newly infiltrated inflammatory dermal Langerin+ DCs (i-Langerin+ dDCs) in AD mouse model induced by topical application of MC903. We found that depletion of i-Langerin+ dDCs only in DTR mice after multiple DT injection resulted in significant reduction of thymic stromal lymphopoietin (TSLP) production and inflammation alleviation, while depletion of LCs or r-Langerin+ dDCs in DTA mice or DTR mice with single DT injection resulted in no significant inflammation changes compared to the wild-type (WT) mice. DT-treated DTR-WT mice with depletion of BM-derived i-Langerin+ dDCs resulted in markedly lower inflammation than that of controls, while PBS-treated chimeric mice (DTR-WT) with only depletion of r-Langerin+ dDCs had a comparable inflammation to WT mice. Furthermore, we found that TSLP contributed to the upregulation of Langerin expression in bone marrow derived DCs and promoted the maturation of Langerin+ DCs. The current study demonstrated that the newly infiltrated inflammatory dermal Langerin+ DCs were essential for TSLP production, which conversely promoted the production of BM-derived i-Langerin+ dDCs, and participated in the inflammation of AD.